Clinical features, Cardiac magnetic resonance imaging findings and outcome of patients with suspected myocarditis - Iqbal, Salik Ur Rehman; Fateh Ali Tipoo Sultan (Journal of the Pakistan Medical Association, 2021)
Myocarditis is largely underdiagnosed due to subclinical symptoms and non-availability of diagnostic techniques necessitating high index of suspicion and early disease identification. This study aimed to assess the clinical presentation, cardiac magnetic resonance (CMR) imaging findings and prognosis of these patients. After reviewing the CMR data of Aga Khan University Hospital from January 2011 to December 2019, a total of 24 patients were included with the confirmed diagnosis of myocarditis on CMR. Mean age was 33.4 +15 years with the majority (58%) being male. Dyspnea (n = 15, 62%) was the commonest symptom followed by chest pain (n = 13, 54%). On echocardiogram, 55% showed LV dysfunction. Common CMR findings were late gadolinium enhancement (n=18, 75%) and bright T2 signals (n=11, 45%). With a mean follow-up of 3.6 + 2.0 years, one patient died of non-cardiac cause. More than half (60%) had resolution of LV dysfunction suggesting favorable prognosis. Continuous...